(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article traces the influence of political trends on the formation and development of ethnosociology in the social sciences in Russia. The foundations of the positivist paradigm in which the ethnosociological direction was formed are revealed, which is associated with the dominant state ideology of Marxism-Leninism in the Soviet period. The grounds for turning to constructivist concepts in the context of integration with the world scientific community in the context of democratization initiated by the central government in the post-Soviet period are shown. The modern discussion within the sociological field is considered, revising the conceptual background of Russian ethnosociology, in the context of political turbulence of recent years.